The coagulant response in sepsis and inflammation - Levi, M. (Hämostaseologie, 2010)
Critically ill patients often have systemic activation of both inflammation and coagulation. Increasing evidence points to an extensive cross-talk between these two systems, whereby inflammation not only leads to activation of coagulation, but coagulation also considerably affects inflammatory activity. The intricate relationship between inflammation and coagulation may have major consequences for the pathogenesis of microvascular failure and subsequent multiple organ failure, as a result of severe infection and the associated systemic inflammatory response. Molecular pathways that contribute to inflammation-induced activation of coagulation have been precisely identified. Activation of the coagulation system and ensuing thrombin generation is dependent on an inter-leukin-6-induced expression of tissue factor on activated mononuclear cells and endothelial cells and is insufficiently counteracted by tissue factor pathway inhibitor. Simultaneously, endothelial-bound anticoagulant mechanisms, in particular the protein C system and the antithrombin system, are shut-off by pro-inflammatory cytokines. Modulation of inflammatory activity by activation of coagulation also occurs by various mechanisms. Activated coagulation proteases, such as the tissue factor-factor VIIa complex, factor Xa and thrombin can bind to protease-activated receptors on various cells and the ensuing intracellular signaling leads to increased production of pro-inflammatory cytokines and chemo kines. Physiological anticoagulants can modulate inflammatory activity as well. Increasing knowledge on the various mechanisms underlying activation of inflammation and coagulation may lead to better (adjunctive) management strategies in critically ill patients.
Keywords: Coagulation; sepsis; inflammation